2018
DOI: 10.1007/s11626-018-0264-4
|View full text |Cite
|
Sign up to set email alerts
|

l-carnosine induces apoptosis/cell cycle arrest via suppression of NF-κB/STAT1 pathway in HCT116 colorectal cancer cells

Abstract: L-carnosine, a dipeptide of the amino acids β-alanine and histidine, is found in various tissues, such as the central nervous system and skeletal muscles. Recently, L-carnosine has been reported to possess anti-tumor activity; however, the molecular mechanism underlying its activity in colorectal cancer is still unknown. Therefore, we investigated the effect of L-carnosine using a human colorectal cancer cell line, HCT116. Treatment with L-carnosine (0, 100, or 200 mM) for 24 h gradually reduced cellular proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
1
18
0
5
Order By: Relevance
“…tified role of carnosine occurring during digestion with a likelihood of protection first for the GIT itself considering among others the reported antiproliferative effect of carnosine on gastric and colorectal cancer cells(Cheng et al, 2019;Lee et al, 2018). The results, in addition, raise the possibility that the effects of carnosine in the GIT could potentially contribute further outside the GIT.…”
mentioning
confidence: 81%
“…tified role of carnosine occurring during digestion with a likelihood of protection first for the GIT itself considering among others the reported antiproliferative effect of carnosine on gastric and colorectal cancer cells(Cheng et al, 2019;Lee et al, 2018). The results, in addition, raise the possibility that the effects of carnosine in the GIT could potentially contribute further outside the GIT.…”
mentioning
confidence: 81%
“…There are only few studies reporting some possible mechanisms of the effects of CAR on the cell cycle of cancer cells, and these do not mention if the effects on the cell cycle were the result of adding CAR to the growth culture media at a single time point or at several times during cell culture 31,33,46 . No information is available regarding the effects of CAR on cell cycle progression of normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…CAR also reduced the extracellular acidification rate and glycolysis 32 . CAR induced apoptosis/cell cycle arrest in human colorectal cancer cells by suppressing of NF-κB/STAT1 signaling 33 .…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, Antognelli et al have demonstrated that AG treatment in ATC cell line is able to revert the pro-tumorigenic role of MGO and this effect is enhanced when AG is used in combination with resveratrol, a Glo1 activator (46). L-Carnosine (b-alanyl-L-histidine), a naturally occurring dipeptide acting as MGO scavenger, has been shown to exert antiproliferative effects in cancer cells (113,114). It reverses MGO protumorigenic action by decreasing migratory ability of breast cancer cells (43,67) and inducing apoptosis in CRC cells, both in vitro and in vivo (44).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%